Studies on the Fibrinolytic System in Human Plasma: Quantitative Determination of Plasminogen Activators and Proactivators - Kluft, C (Thrombosis and Haemostasis, 1979)
Effects due to plasma plasminogen activators and proactivators are usually studied in assay systems where inhibitors influence the activity and where the degree of activation of proactivators is unknown. Quantitative information on activator and proactivator levels in plasma is therefore not availableStudies on the precipitating and activating properties of dextran sulphate in euglobulin fractionation presented in this paper resulted in the preparation of a fraction in which there was optimal recovery and optimal activation of a number of plasminogen activators and proactivators from human plasma. The quantitative assay of these activators on plasminogen-rich fibrin plates required the addition of flufenamate to eliminate inhibitors. The response on the fibrin plates (lysed zones) could be coverted to arbitrary blood activator units (BAU). Consequently, a new activator assay which enables one to quantitatively determine the plasma level of plasminogen activators and proactivators together is introduced.Two different contributions could be distinguished: an activity originating from extrinsic activator and one originating from intrinsic proactivators. The former could be assayed separately by means of its resistance to inhibition by Cl-inactivator. Considering the relative concentrations of extrinsic and intrinsic activators, an impression of the pattern of activator content in plasma was gained. In morning plasma with baseline levels of fibrinolysis, the amount of extrinsic activator was negligible as compared to the level of potentially active intrinsic activators. Consequently, the new assay nearly exclusively determines the level of intrinsic activators in morning plasma. A pilot study gave a fairly stable level of 100 ± 15 BAU/ml (n = 50). When fibrinolysis was stimulated by venous occlusion (15 min), the amount of extrinsic activator was greatly increased, reaching a total activator level of 249 ± 27 BAU/ml (n = 7).